Estresse, coping, burnout, sintomas depressivos e hardiness em residentes médicos - Bolzan, Maria Elaine de Oliveira (2012)
It is a cross-sectional study with quantitative approach aiming to analyze stress, coping strategies, burnout, depression symptoms, and hardiness in medical residents of a Federal University in the interior of Rio Grande do Sul. The research protocol comprises a form for individual characterization of subjects, with sociodemographic variables and functional instruments for stress assessment (Scale of Stress at Work), coping (Coping Strategy Inventory), depressive symptoms (Beck Depression Inventory), burnout (Maslach Burnout Inventory), and hardiness (Hardiness Scale). The instrument application was carried out from February 15th to April 30th, 2011. The subjects answered individually after signing the Term of Free and Highlighted Consent. A database was created in Excel (Office 2007) for data organization and storage. The socio-demographic and functional variables and the items which comprise the instruments were statistically analyzed with the software SPSS versão 18.0 and SAS 9,02. The internal consistency of scales, when evaluated by Cronbach s Alpha Coefficient testified reliability for measuring and evaluating the constructs that are proposed with values ranging from 0.78 to 0.92. The population consisted of 112 medical residents, with the prevalence of single males, aged between 26 and 30 years old, childless, living with the family, playing sports, having leisure activity and being pleased with medical residence. In this study, 58.04% of the subjects presented moderate stress, the stressor with highest mean was working for continuous hours and the lowest average was the superior avoiding entrusting .important responsibilities. The coping strategies which comprise Factor of Resolution of Problems were the most used, and the least utilized comprise the Factor Clash. From the subjects, 29.46% showed high emotional exhaustion, high depersonalization, and low professional performance, with a suggestive picture of burnout. Regarding to depressive symptoms, 88.39 % of the residents are within normal limits. From the residents, 23.21 % presented high means in the domains commitment, control and challenge and are considered hardy individuals. A significant high positive correlation was found between stress and emotional exhaustion, moderate with depressive symptoms and significant negative moderate with professional performance, commitment and control. There was no significant correlation between stress and social support, positive reappraisal and problem solving. For the coping there was a high significant positive correlation between social support and responsibility acceptance. For burnout we established significant high positive correlations between emotional exhaustion and depersonalization and high significant negative between professional accomplishment and emotional exhaustion. The Hardiness Domains presented one another positive significant correlations from moderate to low. It is considered that the stress presents itself as a challenge in the work activity of medical residents who use physical and cognitive efforts in order to adjust to the environmental and professional demands, from the assessment of stressors and coping strategies listed. It was confirmed that the hardy individuals present low scores of stress, use coping strategies focused in the problem and have a meaning sense that opposed to burnout and to depressive symptoms.